Revitalization of thematic villages through red ginger cultivation in Mulyorejo Village, Malang City - Sufiyanto Sufiyanto; Sari Yuniarti; Pindo Tutuko; Sunarjo Sunarjo; Djoko Andrijono; Ahmad Rivaldi; Erika Elice; Antalita Kirana Putri (Universitas Muhammadiyah Magelang, 2024)
The Covid-19 pandemic has significantly impacted society, causing an economic crisis. The thematic village program is a community empowerment effort based on the unique potential characteristics of local communities. This community service program aims to strengthen the concept of thematic villages through the revitalization of the Ginger Red Thematic Village in RW 07, located in Mulyorejo Village, Sukun District, Malang City. The methods applied include outreach, assistance, and improvement of urban farming facilities for red ginger cultivation. The results of this community service program show that the revitalization of the Red Ginger Thematic Village has succeeded in increasing the function of the greenhouse, supporting the urban farming program, and increasing the number of successfully cultivated red ginger plants by the local community. This program represents a significant step in supporting economic recovery and community empowerment amidst the crisis caused by the Covid-19 pandemic.